Demo: Project “Rewind” - Marlokov, Simeon; Karadecheva, Maria (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2015)
This demo covers the concept of preserving our historical consciousness in the vast and never stopping world, attracting the attention of younger generations by creating a game connected to different historical heritage sites.